Humanistic Relationships of Qur’anic Teachers in Fostering a Comfortable Learning Environment for Qur’anic Recitation - Khairiah Khairiah; Ahmad Ridwan (Hikmah, 2025)
This study examines the humanistic relationships established by Qur’anic teachers in fostering a comfortable learning environment for Qur’anic recitation. The study employed a qualitative approach with a descriptive design to explore teacher–learner interactions, individualized guidance, emotional support, and spiritual reinforcement during tahsin learning. Data were collected through participatory observation, semi-structured interviews, and documentation, involving Qur’anic teachers and adult learners at Griya Fadhillah Medan. Data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, with source and technique triangulation used to ensure data credibility. The findings indicate that humanistic relationships are manifested through warm communication, patience, empathy, individualized attention, constructive correction, and positive reinforcement. These practices create psychological safety that enables learners to practice Qur’anic recitation without excessive fear of making mistakes. Individualized guidance through talaqqi and musyafahah also allows teachers to accommodate differences in learning abilities and pace. Furthermore, integrating spiritual values strengthens the meaning and purpose of Qur’anic learning. The study concludes that humanistic relationships are essential for creating a supportive, comfortable, and meaningful environment for sustained engagement in Qur’anic recitation.